Study of time dynamics of erosion processes in the high mountains of Greater Caucasus by satellite information - Mardanov, Ilham Ildirim Oglu (Geodesy and Cartography, 2023)
This work is devoted to the results of comparative visual analysis and instrumental processing of space and aerial photographs of the Azerbaijani part of the Greater Caucasus Lateral Range to assess the relief conditions affecting the formation of high mountain landscapes. The development of exogenous processes in the mountain-meadow and subnivalnival belts in this area has a great impact on the transformation of high mountain landscapes, degradation of soil and vegetation. There is a certain territorial and time differentiation in the intensity of these processes.